Supporting the Design of Systems for Energy Recovery from Mechanical Vibrations Containing MFC Piezoelectric Transducers - Marek Płaczek; Łukasz Dulat (Applied Sciences)
The aim of this research work was to develop and experimentally validate tools to support the design and manufacture of systems that recover electrical energy from mechanical vibrations using non-classical composite piezoelectric transducers. For this purpose, a mathematical model of this type of system was developed, which was then combined with computer-aided engineering tools and the application of the finite element method. In order to verify the obtained results, a test rig was set up to test the vibrations of the system under consideration and its energy efficiency. The results obtained were collated to determine the accuracy of the simulating the operation of piezoelectric transducers acting as electricity generators. The developed tools can be used to support engineering work in the design and manufacture of systems for the recovery of electrical energy from mechanical vibrations, with a view to maximising their operating efficiency under the assumed operating conditions.